Reconstructing Restorative Justice-Based Law Enforcement to Strengthen Substantive Justice and Sustainable Peace in Indonesia - Muhammad Nizar Siradjuddin; Amri Panahatan Sitohang (Journal of Law, Society and Living Norms, 2026)
The retributive model that dominates Indonesia’s criminal justice system has struggled to address prison overcrowding, low victim satisfaction, and weak offender accountability. These structural problems indicate a gap between formal legal certainty and the substantive justice expected by society. This study examines how restorative justice can be normatively reconstructed to strengthen both substantive justice and sustainable peace. Using a normative juridical method supported by conceptual, statutory, and comparative approaches, the analysis demonstrates that current regulations, such as the Juvenile Criminal Justice System Law and Police Regulation Number 8 of 2021, remain fragmented and insufficient to guide consistent implementation. The findings show that restorative justice provides a more relational, victim-centered, and accountability-based framework, but its effectiveness depends on legal coherence, institutional capacity, and safeguards against misuse. Comparative insights from New Zealand and Canada confirm that structured restorative models can reduce recidivism and improve legitimacy when adapted to local contexts. This study concludes that reconstructing restorative justice within Indonesia’s criminal justice policy is essential to align law enforcement with substantive justice and long-term social harmony.